2008
DOI: 10.1089/pho.2007.2197
|View full text |Cite
|
Sign up to set email alerts
|

Role of Nitric Oxide in the Visible Light-Induced Rapid Increase of Human Skin Microcirculation at the Local and Systemic Level: I. Diabetic Patients

Abstract: Both types of irradiation stimulated microcirculation at the local and systemic levels through a mechanism of enhancement of endothelium-dependent and endothelium-independent vasodilation, in which nitric oxide plays a major role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 24 publications
0
20
1
Order By: Relevance
“…15 Because decrements in skeletal muscle contractile function may be associated with inadequate blood flow, it can be postulated that lasermediated vasodilation is responsible for the enhanced skeletal muscle function and the attenuated strength loss. 9,10,16,17 Maegawa et al 9 investigated the effect of light therapy on rat mesenteric microcirculation in vivo and showed vastly improved vasomotor relaxation and, consequently, improved blood flow. Ihsan 18 observed accelerated collateral circulation and enhanced microcirculation in rabbits exposed to light therapy after femoral artery occlusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Because decrements in skeletal muscle contractile function may be associated with inadequate blood flow, it can be postulated that lasermediated vasodilation is responsible for the enhanced skeletal muscle function and the attenuated strength loss. 9,10,16,17 Maegawa et al 9 investigated the effect of light therapy on rat mesenteric microcirculation in vivo and showed vastly improved vasomotor relaxation and, consequently, improved blood flow. Ihsan 18 observed accelerated collateral circulation and enhanced microcirculation in rabbits exposed to light therapy after femoral artery occlusion.…”
Section: Discussionmentioning
confidence: 99%
“…Investigators [4][5][6][7] have begun to explore the ergogenic effects of NIR light therapy in reducing skeletal muscle fatigue and attenuating strength loss during and after resistance exercise. Previous authors [8][9][10] have provided evidence for the ability of light therapy to enhance blood circulation, resulting in an increase in tissue oxygenation. Increasing circulation in the irradiated tissue can lead to enhanced oxygen and substrate delivery, thereby improving the overall ability of the muscle to perform work.…”
mentioning
confidence: 99%
“…How light promotes tissue repair is not fully known, but treatment with light has repeatedly been shown to promote fibroblast proliferation, collagen synthesis, and related granulation tissue formation, as well as the underlying metabolic processes that enhance collagen formation, ATP synthesis, and lymphocytic action (7,8). Furthermore, phototherapy has been shown to promote blood flow and the formation of new blood vessels in experimental animal models of injury and repair (12). A recent study reported that combined 660 and 890 nm LED phototherapy promoted healing of diabetic leg ulcers that failed to respond to other therapies.…”
Section: Discussionmentioning
confidence: 99%
“…PBM therapy has been shown to enhance cellular function, tissue repair, and recovery after injury, disease, or trauma [1][2][3][4][5][6][7][8][9]. One form of PBM therapy that is gaining popularity in clinical medicine is near-infrared (NIR) light therapy.…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence from both basic science and applied studies that PBM therapy may ameliorate disease processes by enhancing blood flow [6][7][8][13][14][15][16] and mitochondrial respiratory chain activity [9,17,18] to and within pathologic tissues.…”
Section: Introductionmentioning
confidence: 99%